(untitled) (MSW Management Journal, 2026)
The rapid expansion of financial technology (FinTech) has transformed the digital payment ecosystem in India, particularly after the 2016 demonetization initiative. Government-led digital initiatives, expanding internet penetration, and the growth of mobile-based payment systems have significantly accelerated the transition toward a cashless economy. In this evolving landscape, women entrepreneurs are increasingly adopting digital payment platforms to enhance business efficiency, transparency, and financial inclusion. However, alongside the benefits of convenience, speed, and accessibility, digital adoption also presents challenges such as cybersecurity risks, digital literacy gaps, and infrastructural constraints. This study examines fintech inclusion and digital payment adoption among women entrepreneurs, with special reference to their awareness, usage behavior, satisfaction levels, and challenges encountered in digital financial transactions. The research is based on primary data collected through structured questionnaires from women entrepreneurs engaged in small and medium-scale enterprises. Analytical tools such as percentage analysis, chi-square test, ranking analysis, correlation, and regression were used to interpret the data. The findings reveal a positive attitude toward digital payment systems, though concerns related to security, technical issues, and awareness gaps persist. The study highlights the need for targeted digital literacy initiatives, secure fintech infrastructure, and policy support to strengthen financial inclusion among women entrepreneurs in 2026 and beyond.